Comparison of personal pronouns in Indonesian and Uzbek languages - Sarieva Zamira (Academia Open, 2019)
The role of pronouns is to replace nouns or noun phrases in the sentences. Personal pronouns replace proper and common nouns, so we do not have to repeat them. This article compares personal pronouns in Indonesian and Uzbek languages. The most important point in the analysis is cultural aspect and its influence on the usage of personal pronouns. The article will reveal the influence of such cultural aspects like politeness and kinship based on example of personal pronoun "you" in Indonesian and Uzbek languages. Influence of formal and informal speech on denoting personal pronouns in Indonesian and Uzbek languages. The analysis will occur on the basis of examples that were taken from the sources which are given in the references.